THE INFLUENCE OF FOREIGN OBJECT DEBRIS (FOD) HANDLING ON FLIGHT SAFETY IN THE APRON AREA BY APRON MOVEMENT CONTROL (AMC) OFFICERS - Gilang Ramadhan, M. Satriatama; Iswahyudi, Prasetyo; Musadek, Ahmad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Apron Movement Control (AMC) is a unit found at the airport that has the responsibility to oversee all movements on the apron. Therefore the task of an AMC unit employee is to inspect the airside area to ensure that there is no Foreign Object Debris (FOD) so that flight safety is carried out at Radin Inten II International Airport Lampung. The objective of this study is to investigate whether the management of FOD by AMC officers has an impact or not to flight safety at Radin Inten II International Airport Lampung This is because FOD is still found in the airport apron area which even has an impact on flight delays at the airport. The hypothesis of this study is that the handling of FOD by AMC officers in the Apron area has an influence or not on flight safety at Radin Inten II International Airport Lampung. The research method used is quantitative. Determination of the sample was taken from the total population of 30 people consisting of AMC officers, PKP-PK officers, as well as building and runway officers. The data Approach for collecting data utilized a Likert scale questionnaire which was distributed to the sample and then the data was processed using a regression analysis test and a correlation test which previously carried out analysis prerequisite tests including validity evaluations, reliability tests and normality tests using the Statistical Package for the Social Sciences (SPSS) application. Thus, based on the findings of the several tests above, one can ascertain that FOD handling by AMC officers in the Apron area can have an impact on flight safety at Radin Inten II International Airport, Lampung. Of course by implementing various ways to improve flight safety, for example by rearranging the shifts of AMC officers on the morning and afternoon shifts and providing special FOD bins.